Secondary School EFL Teachers' Perceptions and Experiences of Professional Development - Arif Rahman; Mirjam Anugerahwati; Sri Rachmajanti (Graduate School of Universitas Negeri Malang, 2022)
Abstract: Professional development (PD) is not just a short involvement but a long process starting from teacher training at university and going on throughout the working life of the individuals. This study assessed the perceptions and experiences of upper secondary school EFL teachers. A semi-structured interview was used to gather the data from 5 teachers from different schools. The findings revealed that teachers were aware of the significance and necessity of PD and saw it as a process that helped them to be more knowledgeable and experienced teachers. They also pointed out that involving in such studies could help them professionally.Abstrak: Pengembangan profesi guru bukan merupakan proses singkat melainkan sebuah proses yang panjang yang dimulai dari bangku kuliah yang berlanjut hingga dunia kerja seorang individu. Penelitian ini mengulas tentang presepsi dan pengalaman guru bahasa inggris tingkat SMA perihal pengembangan profesi guru. Interview digunakan untuk mendapatkan data dari 5 guru dari 4 SMA yang berbeda. Hasil dari penelitian ini menyimpulkan bahwa guru guru bahasa inggris tingkat SMA menyadari akan pentingnya dan perlunya mereka dalam hal pengembangan keprofesian dan memandang hal tersebut sebagai proses untuk menjadi guru yang memiliki banyak pengetahuan dan guru yang perpengalaman.